Mentoring as prevention of early school leaving: a qualitative systematic literature review - Fehérvári, Anikó; Varga, Aranka (Frontiers in Education, 2023)
One of the biggest challenges facing education systems is preventing early school leaving. Not completing secondary education has serious long-term negative consequences for both individuals and society. There is currently a wide body of empirical literature that reviews the causes of and risk factors for school dropout and the prevention of student attrition. With new reviews emerging over time, our analysis updates previous systematic analyses, and we therefore review empirical studies from seven databases between 2013 and 2021 that use mentoring to prevent early school leaving. We focus on mentoring because personal support is a crucial type of prevention program. We identified 25 studies from this period through a systematic search. The aim of our research was to identify the target groups, the mentoring roles, and the goals and outcomes of the mentoring programs in the interventions undertaken in the studies we identified. The studies present both school-based and community-based mentoring practices primarily in North American and European countries. The results show that the focus of the studies was mainly on secondary school target groups as there were few studies addressing younger age groups. Most of the studies focused on a one-year period or shorter durations, and several studies found that mentoring had positive effects on students. However, not all the factors identified as development objectives have changed. It should also be stressed that the success of mentoring depends on the quality of the mentors and the quality of their relationship with the mentees, as well as on the implementation of the mentoring programs and the school contexts in which they operate. The importance of the latter has perhaps received less attention in previous reviews and analyses.